2017
DOI: 10.1007/s10826-017-0810-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relationship between Religiosity and Caregiver–Adolescent Communication About Sex within African-American Families

Abstract: Caregiver-adolescent communication about sex plays a critical role in the sexual socialization of youth. Many caregivers, however, do not engage their youth in such conversations, potentially placing them at risk for negative sexual health outcomes. Lack of caregiver-adolescent communication about sex may be particularly harmful for rural African American youth, as they often report early sex initiation and are disproportionately impacted by STIs. Moreover, sexual communication may be particularly challenging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
(67 reference statements)
0
13
0
Order By: Relevance
“…Discordant responses may be due to the way in which information is communicated with youth, such that caregivers with lower self-efficacy, poorer communication skills, and greater discomfort with PTCS may use language that is less clear and descriptive, expecting youth to pick up on conversational cues (Ritchwood, Penn, et al, 2017; Wilson, Dalberth, Koo, & Gard, 2010). From an adolescent perspective, vague and nonexplicit communications may not be perceived as sexual communication, and could lead youth to be less attentive during such discussions (Ritchwood, Powell, et al, 2017). These discrepancies are important, considering that previous work with early adolescents has shown that significant discordancy between mother child sexual attitudes, along with youths’ tendency to misperceive their mothers’ attitudes about sex, could be connected to greater sexual risk among early adolescents and is likely the result of ineffective or lack of PTCS (Gound et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Discordant responses may be due to the way in which information is communicated with youth, such that caregivers with lower self-efficacy, poorer communication skills, and greater discomfort with PTCS may use language that is less clear and descriptive, expecting youth to pick up on conversational cues (Ritchwood, Penn, et al, 2017; Wilson, Dalberth, Koo, & Gard, 2010). From an adolescent perspective, vague and nonexplicit communications may not be perceived as sexual communication, and could lead youth to be less attentive during such discussions (Ritchwood, Powell, et al, 2017). These discrepancies are important, considering that previous work with early adolescents has shown that significant discordancy between mother child sexual attitudes, along with youths’ tendency to misperceive their mothers’ attitudes about sex, could be connected to greater sexual risk among early adolescents and is likely the result of ineffective or lack of PTCS (Gound et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…There are several potential explanations for these findings. First, discussing sensitive sex topics may require caregivers to acknowledge that their youth are sexual beings and thus, normalize their youths’ sexual nature, which may be inconsistent with caregivers’ beliefs and attitudes (Ritchwood, Powell, et al, 2017). Second, it is possible that caregivers in our study did not believe that such information was relevant or appropriate for early adolescents, as a significant proportion of caregivers in this study also reported low to moderate levels of PTCS about reproductive and sexual health topics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, both teachers and parents highlighted their awareness of possible backlash from more religiously inclined parents but we noted no differences across faith-and non-faith based schools in terms of withdrawal of students from the programme or in reports of engagement with the parent materials. Although faith-based schools and religious parents are sometimes construed in mainstream media as opposed to any kind of RSE, research findings, including this study and our own previous work [3,102], suggest that many are open to school-based RSE in general and most are open to the provision of RSE that is in line with their religious beliefs.…”
Section: Acceptability and Feasibility Of The Jack Digital Parent Matmentioning
confidence: 51%